2012
DOI: 10.1007/s00262-012-1261-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of autologous dendritic cell-based immunotherapy in the standard of care treatment for patients with newly diagnosed glioblastoma: results of the HGG-2006 phase I/II trial

Abstract: Full integration of autologous DC-based tumor vaccination into standard postoperative radiochemotherapy for newly diagnosed glioblastoma seems safe and possibly beneficial. These results were used to power the currently running phase IIb randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 38 publications
0
115
0
1
Order By: Relevance
“…The majority of vaccinations were started within 1 week to 3 months after resection. 3,4,16,32 However, previous reports did not describe the time of initiation of vaccination in detail. 4 In our study, 5 of 6 patients with glioblastoma had PD at the end of the first session of vaccination.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of vaccinations were started within 1 week to 3 months after resection. 3,4,16,32 However, previous reports did not describe the time of initiation of vaccination in detail. 4 In our study, 5 of 6 patients with glioblastoma had PD at the end of the first session of vaccination.…”
Section: Discussionmentioning
confidence: 91%
“…In the past trials, increased peripheral immune markers, such as cytotoxic T-lymphocyte (CTL) activity and positive delayed tissue hypersensitivity (DTH) tests, have been reported, but their correlation with clinical outcomes was weak and therefore they lacked prognostic value. 28,36,38,44,47 Nevertheless Yamanaka et al 37 and Wheeler et al 39 reported some value in measuring such markers, while Fadul et al 44 found that 50% of patients developed a measurable immune response which was associated with improved OS. Currently the most valid indicator of vaccination-induced immune responses to GBM is considered to be tumor infiltration by activated T-cells.…”
Section: Immune Monitoring Of the Productmentioning
confidence: 99%
“…Mean overall survival (OS) ranged between 16.0 and 38.4 months for ND-GBM and between 9.6 and 35.9 months for recurrent GBM. 28, Of interest, Ardon et al 47 analyzed their results based on RPA classification and reported a mean OS of 39.7 months on patients with ND-GBM for RPA class III. Thus, it seems that specific subgroups of GBM patients may benefit from DC-vaccinations greater than others.…”
mentioning
confidence: 99%
“…Dendritic cell based therapeutic approach has now been applied as an adjuvant for the treatment of several types of cancers such as lymphomas (Hsu et al 1996), myelomas (Curti et al, 2007), brain cancers (Ardon et al, 2012) and pediatric malignancies (Dohnal et al, 2007) with some degree of success. Since no uniform standardised protocol has emerged, we developed a protocol and initiated a phase I trial.…”
Section: Discussionmentioning
confidence: 99%
“…A study using DCs against glioma had shown that cytotoxic T cell activity may develop even twelve weeks (Yu et al, 2001) after vaccination while recently another reported CD8+T cell and IFN-γ responses in melanoma patients after they were given multiple DC vaccines loaded with a cocktail of synthetic peptides including MART-1 (Melanoma antigen recognized by autologous T cells-1) (Okoshita et al, 2012). Ardon et al (2012) also noted that DC-based tumor vaccines in booster doses improved the six month progression free and median overall survival of newly diagnosed glioma patients who underwent surgery and concomitant chemoradiotherapy. For sustained stimulation of the immune system through multiple vaccinations, leukapheresis may be the best strategy.…”
Section: Discussionmentioning
confidence: 99%